An Analysis of Zola's' La Conquête de Plassans - Hantle, Ross William (My University, 1972)
An analysis of Zola's La Conquête de Plassans, including notes on the composition and method of characterization, a study of the major socio-political aspects of the novel, and an examination of several recurring metaphorical patterns.
Keywords: Romance Languages; Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures